2007
DOI: 10.1093/jac/dkm231
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the AdeABC efflux system gene content, netilmicin susceptibility and multidrug resistance in a genotypically diverse collection of Acinetobacter baumannii strains

Abstract: The AdeABC genes are common in A. baumannii, but may be absent in some, mostly fully susceptible strains. Decreased susceptibility to netilmicin (MIC 4-32 mg/L) is associated with both the presence of these genes and multidrug resistance and may be indicative of AdeABC overexpression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 18 publications
3
59
0
Order By: Relevance
“…Previously, Nemec et al (2007) found that 82% of A. baumannii isolates from a predominantly European collection carried adeB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, Nemec et al (2007) found that 82% of A. baumannii isolates from a predominantly European collection carried adeB.…”
Section: Discussionmentioning
confidence: 99%
“…Nemec et al (2007) reported that the adeB gene was present in 87% of 116 genetically diverse predominantly European A. baumannii isolates. Other studies dealt with genetically related isolates (Huys et al, 2005b) or worked with a collection from one particular hospital (Chu et al, 2006;Lin et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, the genes encoded RND efflux pumps are mainly located on the chromosome, they are detected with the different frequency [19,41,82]. The gene of the main AdeB transporter was detected by Chu et al [19] with the frequency of the 70% whether the 87% through Nemec et al [82].…”
Section: Genes Of Adeabc System and Functionmentioning
confidence: 99%
“…However, the genes encoded RND efflux pumps are mainly located on the chromosome, they are detected with the different frequency [19,41,82]. The gene of the main AdeB transporter was detected by Chu et al [19] with the frequency of the 70% whether the 87% through Nemec et al [82]. All both structural and two-component regulatory system genes were stated about 40% of examined strains, in the remaining cases all sorts combinations of the presence of these genes were being watched [82].…”
Section: Genes Of Adeabc System and Functionmentioning
confidence: 99%
“…Many clinical A. baumannii isolates harbour different genetic arrangements of the adeRS and adeABC operons 39 . Examination into one A. baumannii clinical isolate identified that insertionalinactivation of the outer membrane component of the pump (AdeC) did not affect resistance towards two previously identified AdeABC substrates 25 .…”
mentioning
confidence: 99%